Flame retardant polyurethane foams with starch unit - Renata Lubczak (Elsevier, 2021)
Polyurethane foams with incorporated starch described in up to date literature have good functional properties except flame resistance. Their oxygen index falls within 19.3–20.5%, while flame rate is 2.25–12.50 mm/s. We have obtained and tested polyurethane foams with following flame retardants: melamine, and two phosphoric(V) acid esters: Fyrol PNX and Fyrol PCF. The functional properties of the flame retardant modified foams were compared with non-modified foams using horizontal flaming tests, determination of oxygen index and combustion in microcalorimeter. According to horizontal flaming tests all modified foams were self-extinguishing. The oxygen index of modified foams was within 22.9–24.4%. The foams could stand long-term heating at 150 °C temperature. Moreover, the polyurethane foams have a biodegradation potential.